Diversity of archaeal and bacterial communities on exfoliated sandstone from Portchester Castle (UK). (April 2016) - Zanardini, Elisabetta; May, Eric; Inkpen, Robert; Cappitelli, Francesca; Murrell, J. Colin; Purdy, Kevin J.
Abstract: In this study exfoliated sandstone samples from Portchester Castle were investigated using scanning electron microscopy (SEM) and energy dispersion X-ray (EDX) analyses to observe stone surface colonisation, geomorphological structure and to assess damage. Archaeal and bacterial diversity were assessed using cultivation-dependent and cultivation-independent methods. SEM analysis showed that sandstone had high levels of stone decay. There was considerable weathering of the minerals associated with biofilms containing microbes with various cellular morphologies. Microorganisms were especially prevalent in pores, cavities and in the heavily decayed parts of the minerals, and some etching was seen. EDX analyses indicated microbes were associated with the sheet structures of aluminium-containing phyllosilicate minerals, most likely glauconite. Microbial colonisation was preferentially concentrated within specific sheets of the mineral structure. Isolation studies revealed the presence of Bacillus and Arthrobacter that appeared to be well adapted to "extreme" environments, specifically these isolates were tolerant to high salt, high UV and oligotrophic conditions. Cultivation-independent studies using denaturing gradient gel electrophoresis fingerprinting of bacterial and archaeal 16S rRNA gene fragments showed a more complex community. Chloroflexi, Actinobacteria, Deinococcus, α- and β-proteobacteria, Cyanobacteria and Bacteroidetes and halophilic Archaea from the family Halobacteriaceae, were the predominant types of Bacteria and Archaea detected respectively. Highlights: Integrated approach revealed complex microbial colonisation in altered sandstone. Most of the microorganisms are well adapted to extreme environments. Identity of key players that cause damage is vital to conserve heritage stonework.